A novel oxygen vacancy introduced microstructural reconstruction of SnO2-graphene nanocomposite: Demonstration of enhanced electrochemical performance for sodium storage. (20th August 2018) - Lu, Xiaoxiao; Mao, Qinan; Chen, Yifan; Bao, Liang; Tong, Lincong; Xiong, Qinqin; Qin, Haiying; Pan, Hongge; Ji, Zhenguo
Abstract: This paper reported an oxygen vacancy contained SnO2 -graphene nanocomposite (OVs-SnO2 -Gr), which was prepared by annealing SnO2 -graphene nanocomposite in 3 vol% H2 /Ar atmospheres. It demonstrated with a high reversible capacity of around 510 mAh g −1 after 300 cycles at a current density of 40 mA g −1, and an impressive reversible rate performance of 391 mAh g −1 can be obtained even at a high current density of 1200 mA g −1 when applied as anode for sodium storage. Evidenced by a new phase of Na2 SnO3 during sodium storage reactions, it is found that sodium can insert into crystal lattice of oxygen vacancy contained SnO2 . Moreover, sodium insertion could arouse a novel structural reconstruction and introduce amorphous phase SnO2, which promotes the surface-controlled reaction process and Na + diffusion rates, and enables a good rate performance. Additionally, the H2 /Ar annealing process increases overall conductivity of electrodes, which further reduces the barrier of Na + diffusion. It is believe that the as-prepared OVs-SnO2 -Gr is a promising anodes for Na-ion batteries with outstanding electrochemical performance. Graphical abstract: Image 1 Highlights: Oxygen vacancies (OVs) contained SnO2 -Gr is prepared by annealing in H2 /Ar. The OVs-SnO2 -Gr is demonstrated with an enhanced rate capacity. OVs introduced a new phase of Na2 SnO3 and novel structural reconstruction. The OVs-SnO2 -Gr demonstrated with increased reaction kinetics.